Uncovering exposome-related diseases through the pathologic metallome: a novel approach for clinical populations - Leinardi, Riccardo; Huaux, François (Frontiers in Toxicology, 2025)
Environmental exposure to complex metal mixtures plays a critical role in the onset and progression of diverse chronic diseases, in ways that the traditional toxicological framework fails to capture. A paradigm shift is underway, moving toward a more integrated understanding of combined metal effects through the interdisciplinary study of the metallome, the distribution of metal ions and metalloids within a biological system. In this perspective, we highlight the clinical importance of metallome to identify specific subpopulations in which disease onset or progression is primarily driven by environmental metal exposure rather than genetic predisposition. To achieve this goal, robust and sensitive analytical methods are required to overcome the limitations of conventional approaches and enable the detection of the full spectrum of metal species, including metals sequestered within mineral particles present in body fluids and tissues. We propose methodological innovations in sample preparation and analysis that expand the current scope of metallome-associated research. Together, these advances support a comprehensive framework for assessing metal mixture effects in environmental health, bridging toxicology with clinical practice and enabling more targeted, exposure-informed public health interventions.